Embolization of a Bleeding Duodenal Arteriovenous Malformation with a Conformable Embolic Material (Obsidio): Case Report - Kalei Hering; Patrick Sutphin; Sanjeeva Kalva (Journal of Clinical Interventional Radiology ISVIR)
We report a case of duodenal arteriovenous malformation (AVM) that was successfully treated with a conformable embolic material. A 69-year-old woman presented with acute gastrointestinal bleeding with associated hemodynamic instability. Computed tomography demonstrated active bleeding from the duodenum. Endoscopy showed angioectasia in the duodenum and small bowel. Angiography revealed a simple, but actively bleeding AVM in the duodenum fed by the inferior pancreaticoduodenal artery, a nidus, and an outflow vein that drained into the portal vein. A conformable embolic material (Obsidio) was utilized to occlude the nidus and the feeding artery, resulting in hemodynamic stability and complete occlusion of the AVM.